MODEL THINK, PAIR AND SHARE UNTUK MENINGKATKAN PENALARAN MATEMATIS SISWA SMP LABORATORIUM UM KELAS VII - Latifah Mustofa Lestyanto; Lailatul Mubarokah (FMIPA UNIVERSITAS NEGERI MALANG, 2021)
The purpose of this study was to describe the TPS model to improve students' mathematical reasoning abilities. This study uses the PTK method from Kemmis-Mc. Taggart. The stages of the research carried out were the stage of disease development, the planning stage, the implementation stage, the observation stage, and the reflection stage. The results of this study indicate that the activity stages of the TPS learning model that can improve students' mathematical reasoning in the PLSV and PtLSV material are (1) Think, at this stage students can optimize their thinking power by working on individual worksheets so as to encourage students to reason. (2) Pair, at this stage students discuss in pairs and cause students to think more critically so that it can improve students' mathematical reasoning. (3) Share, at this stage students present the results of their discussion in front of the class and the teacher provides answers.